Green Tech Enterprise / Mohd Izzanur Rashidi...[et.al] - Rashidi, Mohd Izzanur; Ahmad Fauzi, Mohd Farid; Norjim, Norhanisah; Hasnan, Nur Hanisah; Mohamad Amin, Siti Alsyah (Faculty of Plantation and Agrotechnology, 2016)
Green Tech Enterprise is a company that involve in the agriculture business where there are a lot of technologies that already exists and are about to be invented and explore as there are a lot of new things that had been done as the advancement of technology has begun to encourage our country to be more open in term of critical thinking and the acceptance and awareness of new technology. From what we know, the agriculture sector has begun the new revolution in term of managements, systems and technology which the current scenario involves the adolescence to participate in the agriculture field. Based on the current scenario that had been .